Analisis Singkapan Batuan Pasca Pengambilan Bahan Galian Di Pulau Buton - Asrim Asrim (Jurnal Geomine, 2020)
Rock outcrop is one type of geological data that often used in mining to determine rock types. Besides that rock outcrops can also be used to find out how strong a rock even though rock mechanics have not been tested. Rock strength depend on various factors, one of which is lithology. One of the physical parameters that describes rock strength is density. Each rock type has different density. The purpose of study is to determine lithology or rock type after extracting the minerals. The rock outcrop as object of the study is the rock wall after the extraction of the rock material which is located in Baubau City, Buton Island. The research method was carried out by observing rock physical properties and correlating the rock type with the rock density. The interpretation of rock outcrops is focused on observing the physical features and rock minerals. Based on the analysis, the rock outcrop is dominated by limestone. Based on rock type, the density of the rock outcrops ranges from 2.5 g.cm-3 to 2.9 g.cm-3. The variation in density values indicates that the rock outcrop is strong and stable.